Tetraspanins in infections by human cytomegalo- and papillomaviruses. (15th April 2017) - Fast, Laura A.; Lieber, Diana; Lang, Thorsten; Florin, Luise
Abstract : Members of the tetraspanin family have been identified as essential cellular membrane proteins in infectious diseases by nearly all types of pathogens. The present review highlights recently published data on the role of tetraspanin CD151, CD81, and CD63 and their interaction partners in host cell entry by human cytomegalo- and human papillomaviruses. Moreover, we discuss a model for tetraspanin assembly into trafficking platforms at the plasma membrane. These platforms might persist during intracellular viral trafficking.